Regional Integration as “Second-Best” Alernative in Post-Financial Crisis World: Lessons from the European Monetary Union to the Mercosur and Unasur: Integração regional como “segunda-melhor” alternativa no mundo pós-crise financeira: lições da União Monetária Europeia para o Mercosul e Unasul - Saraiva, Renato; Fernández, Thaís Dutra (Conjuntura internacional, 2018)
The International Monetary System does not reflect transformations in the global economy. Being impossible to reform it, economic integration processes may be a “second-best” alternative. By analyzing the European Monetary Union we conclude that MERCOSUR and UNASUR should conceive regimes in less restrictive forms and develop fiscal and political integration.